Photogrammetry as a tool to improve ecosystem restoration. (December 2021) - Ferrari, Renata; Lachs, Liam; Pygas, Daniel R.; Humanes, Adriana; Sommer, Brigitte; Figueira, Will F.; Edwards, Alasdair J.; Bythell, John C.; Guest, James R.
Abstract : Ecosystem restoration has been practiced for over a century and is increasingly supported by the emergent applied science of restoration ecology. A prerequisite for successful ecosystem restoration is determining meaningful and measurable goals. This requires tools to monitor success in a standardized way. Photogrammetry uses images to reconstruct landscapes and organisms in three dimensions, enabling non-invasive measurement of key success indicators with unprecedented accuracy. We propose photogrammetry can improve restoration success by: (i) facilitating measurable goals; (ii) innovating and standardizing indicators of success; and (iii) standardizing monitoring. While the case we present is specific to coral reefs, photogrammetry has enormous potential to improve restoration practice in a wide range of ecosystems. Highlights: Restoration and rehabilitation are essential strategies to promote recovery and adaptation of ecosystems. Clear goals, appropriate indicators, and standardized monitoring of restoration interventions are critical to assess their success, yet these are often lacking or unclear. Photogrammetric three-dimensional reconstructions enable accurate, standardized, and non-invasive measurement of key indicators needed for monitoring of restoration, such as surface area, canopy height, volume, and fractal dimensions of features in a landscape. Photogrammetry can boost the success of restoration interventions by: (i) establishing a baseline to assess success and facilitate goal setting; (ii) innovating and standardizing indicators of success; and (iii) standardizing monitoring of restoration indicators with unprecedented accuracy and precision.